A comparison of high frequency chest wall oscillation and intrapulmonary percussive ventilation for airway clearance in pediatric patients with tracheostomy. Issue 2 (17th February 2017) - Bidiwala, Aneela; Volpe, Linda; Halaby, Claudia; Fazzari, Melissa; Valsamis, Christina; Pirzada, Melodi
ABSTRACT: Objectives : The aim of this study was to compare two modes of airway clearance, the intrapulmonary percussive ventilation system (IPV) to high frequency chest wall oscillation system (HFCWO) in medically complex pediatric patients with tracheostomy requiring long term care. Methods : This was a single center, retrospective study comparing the number of respiratory illnesses, lower respiratory tract infections (LRTI), utilization of bronchodilator and systemic steroids, and respiratory illnesses requiring acute care hospitalizations. A total of 8 tracheostomy dependent patients between the ages of 1–22 years were included for a 2-year study period. Each patient was used as their own control. During the period studied, the only variable in the medical regimen was the modality used for airway clearance. A Poisson regression model and generalized estimating equations were used to compare pre and post rates and to account for the correlation of count data from the same individual. Additionally, the paired differences (post—pre) for each event count were computed to provide the median and range of reductions in event rates while using intrapulmonary percussive ventilation system device. The non-parametric wilcoxon signed-rank test employed to determine whether the results from the Poisson model were consistently observed regardless of method of analysis. Results : The total number of respiratory illnesses were reduced from 32 per year on HFCWO therapy to 15 per year on IPV system therapy (p < 0.001). The total number of LRTI requiring antibiotic use were decreased from 15 per year to 6 per year (p = 0.01), use of bronchodilator treatments were reduced from 53 to 21 (p < 0.001) and utilization of systemic steroids were reduced from 12 to 4 on IPV (p = 0.003). Numbers of hospitalizations to acute care facilities were reduced from 8 to 3 hospitalizations during the period of IPV use for airway clearance (p = 0.003). Conclusion : This study suggests that airway clearance by IPV therapy could be more effective and beneficial in providing airway clearance in specific subsets of the medically complex pediatric population.